Development of SCADA Dynamic Application Design - Joesianto Eko Poetro; M. Basuki Rahmat; Agus Khumaidi; Hananta A; Bhakti Bhakti (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2021)
The COVID-19 pandemic has changed major habits in learning patterns. Before the pandemic, almost all learning activities took place face-to-face. Especially vocational education, where competence or expertise is an absolute achievement that must be achieved. Learning patterns where practical learning reaches 60% of students must obtain practical learning directly. During the pandemic, direct learning activities cannot be carried out in full. This will have an impact on student competence. Solution is needed to solve it. One of them is how students can practice virtually. This article does not discuss the extent of competence achieved by a student through online practice. The focus of this article is to discuss how practical devices can be controlled remotely by designing a virtual system on the platform and running it in real time or known as dynamic application. And technicians or PLP will still supervise the operation of equipment in the laboratory. The device will be built using the MODBUS communication protocol.